Tunne- ja vuorovaikutustaitojen opettamisesta yläkoulun liikuntatunnilla : liikuntapedagogiikan aikuiskoulutuksen maisteriohjelmasta valmistuvien opiskelijoiden kokemuksia ja näkemyksiä - Paajanen, Samu; Ylitalo, Pyry (2024)
The aim of the study was to explore the experiences and perceptions of students graduating from the master's level adult education program in physical education regarding teaching social and emotional skills in upper comprehensive school physical education. Especially, the study sought to determine how these skills are defined by graduating students, as well as how and why they are taught. The purpose of the study was to identify specific methods used by the participants to teach social and emotional skills during upper comprehensive school physical education classes. The topic was chosen due to the topicality of these skills and the researchers' own interest in the subject. The study was conducted as a qualitative case study by using a data-driven approach. The study aimed to uncover other factors related to the phenomenon as well through data-driven approach. The research strategy was phenomenological-hermeneutic. The research data formed of written essays by five students graduating from the master's level adult education program in physical education. The data was collected by Webropol survey tool. Thematic analysis was used as the method of data analysis. Key concepts in the study include social and emotional skills, also referred to as SEL (Social and Emotional Learning) skills. Major theories discussed in the study include Goleman's emotional intelligence and Gordon's theories of interpersonal communication. It was proved in this study that various factors were associated with teaching social and emotional skills as a result of the study. The first factor related to teaching these skills was the participants' definitions of social and emotional skills. The second factor was the target of the impact of teaching social and emotional skills. The term the target of the impact refers to the factors underlying an individual's or group's psychosocial well-being. The third factor was pedagogical solutions meaning how these skills are taught. The fourth factor was the learner and teacher profiles in the teaching situation. The conclusion was that teacher's role by view of graduating students is to create a supportive and trusting atmosphere where the well-being of everyone is promoted through positive interaction and the joy of learning. The teacher enables the overall growth of the student through their own personality, example, and understanding of teaching social and emotional skills, as well as supporting the development of self-esteem. A safe atmosphere and emotional skills reinforce each other.